Nicaragua : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Nicaragua. (IMF Staff Country Reports; Country Report, 2016)
The 2015 Article IV Consultation presents economic outlook and risks of Nicaragua. Over the last three years, real GDP growth has averaged 4.8 percent, one of the highest in the region, while inflation has remained anchored by the exchange rate regime. Poverty has fallen sharply, but unemployment has increased due to a decline in the manufacturing sector. The current policy mix is broadly adequate to maintain macroeconomic stability in the near term, but Nicaragua needs to fortify its policy framework. In particular, reducing tax exonerators and exemptions and improving the targeting of fiscal subsidies would strengthen the efficiency and equity of public finances and contribute to rebuilding fiscal buffers.